2017
DOI: 10.15640/jpbs.v5n1a7
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Indigenous Violent Extremism Beliefs Scale (VEBS)

Abstract: The validation and implications of an indigenously developed Violent Extremism Beliefs Scale (VEBS) is presented. The aim of this study was to develop a tool which can assess violent extremist beliefs. The item pool was generated from case studies of violent extremist offenders who have undergone successful Deradicalization and rehabilitation as well as violent extremist offenders still undergoing this (Deradicalization and rehabilitation) process, interviews of psychologists and social workers working with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, this factor explained only 5% variance. Since there have been an overrated significance attributed to religious intolerance and political attitudes in literature mainly because in the past few decades, it has been observed that violence and extremism in the name of religion have been widely reported (Peracha et al, 2017). Moreover, it is also observed that most of the modern-day incidences of terrorist attacks are perpetrated by self-declared Muslims, or recent converts to Islam.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this factor explained only 5% variance. Since there have been an overrated significance attributed to religious intolerance and political attitudes in literature mainly because in the past few decades, it has been observed that violence and extremism in the name of religion have been widely reported (Peracha et al, 2017). Moreover, it is also observed that most of the modern-day incidences of terrorist attacks are perpetrated by self-declared Muslims, or recent converts to Islam.…”
Section: Discussionmentioning
confidence: 99%
“…The expected correlations exist between Risk Assessment Tool for Extremism (RATE), Violent Extremism Beliefs Scale (VEBS; Peracha et al, 2017), Depression, Stress, and Anxiety Scale (DASS; Lovibond & Lovibond, 1995). These indicate the convergent validity of RFES scale.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Religious Extremism.The researcher adapted the Religious Power Violence and Extremism scale from the Violent Extremism Beliefs Scale (VEBS) [19]. The scale consists of four items with all favorable.…”
Section: Instrumentsmentioning
confidence: 99%